Does board size matters? New evidence from a two-tier board system / Salim Darmadi - Darmadi, Salim (Accounting Research Institute (ARI), Faculty of Accountancy & UiTM Press, 2014)
The objective of this study is to examine the association between board size and firm value using the setting of a developing economy that adopts a two-tier board system. Hence, the present study extends the existing literature which heavily focuses on economies adopting unitary board structure. Employing a sample of non-financial companies listed on the Indonesia Stock Exchange (IDX), we perform regression analyses separately for the supervisory board and the management board. Using return on assets (ROA) and Tobin sQas measures of firm value, our results support the proposition that board size and firm value are positively associated. Across different models and estimation techniques, the relationship of board size to Tobin's Q is more robust than that to ROA. Our further analysis also reveals that larger board size is more likely to be employed by larger firms, which benefit from having larger boards. It is suggested that listed companies need to carefully arrange their board structure in their efforts to maximize firm value.